Detection of CBP rearrangements in acute myelogenous leukemia with t(8;16) - Giles, Rachel Helen; Dauwerse, J. G.; Higgins, C.; Petrij, F.; Wessels, J. W.; Beverstock, G. C.; Döhner, Hartmut; Jotterand-Bellomo, M.; Falkenburg, J. H. F.; Slater, R. M.; van Ommen, G.-J. B.; Hagemeijer, A.; et al. (Leukemia, 1997)
The CREB-binding protein (CBP) is a large nuclear protein that regulates many signal transduction pathways and is involved in chromatin-mediated transcription. The translocation t(8;16)(p11;p13.3) consistently disrupts two genes: the CBP gene on chromosome band 16p13.3 and the MOZ gene on chromosome band 8p11. Although a fusion of these two genes as a result of the translocation is expected, attempts at detecting the fusion transcript by reverse transcriptase polymerase chain reaction (RT-PCR) have proven difficult; to date, only one in-frame CBP/MOZ fusion transcript has been reported. We therefore sought other reliable means of detecting CBP rearrangements. We applied fluorescence in situ hybridization (FISH) and Southern blot analyses to a series of AML patients with a t(8;16) and detected DNA rearrangements of both the CBP and the MOZ loci in all cases tested. All six cases examined for CBP rearrangements have breakpoints within a 13 kb breakpoint cluster region at the 5′ end of the CBP gene. Additionally, we used a MOZ cDNA probe to construct a surrounding cosmid contig and detect DNA rearrangements in three t(8;16) cases, all of which display rearrangements within a 6 kb genomic fragment of the MOZ gene. We have thus developed a series of cosmid probes that consistently detect the disruption of the CBP gene in t(8;16) patients. These clones could potentially be used to screen other cancer-associated or congenital translocations involving chromosome band 16p13.3 as well.